-7(v+4)+3v+7=8v+6

Simple and best practice solution for -7(v+4)+3v+7=8v+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(v+4)+3v+7=8v+6 equation:


Simplifying
-7(v + 4) + 3v + 7 = 8v + 6

Reorder the terms:
-7(4 + v) + 3v + 7 = 8v + 6
(4 * -7 + v * -7) + 3v + 7 = 8v + 6
(-28 + -7v) + 3v + 7 = 8v + 6

Reorder the terms:
-28 + 7 + -7v + 3v = 8v + 6

Combine like terms: -28 + 7 = -21
-21 + -7v + 3v = 8v + 6

Combine like terms: -7v + 3v = -4v
-21 + -4v = 8v + 6

Reorder the terms:
-21 + -4v = 6 + 8v

Solving
-21 + -4v = 6 + 8v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '-8v' to each side of the equation.
-21 + -4v + -8v = 6 + 8v + -8v

Combine like terms: -4v + -8v = -12v
-21 + -12v = 6 + 8v + -8v

Combine like terms: 8v + -8v = 0
-21 + -12v = 6 + 0
-21 + -12v = 6

Add '21' to each side of the equation.
-21 + 21 + -12v = 6 + 21

Combine like terms: -21 + 21 = 0
0 + -12v = 6 + 21
-12v = 6 + 21

Combine like terms: 6 + 21 = 27
-12v = 27

Divide each side by '-12'.
v = -2.25

Simplifying
v = -2.25

See similar equations:

| 4x=11.4285 | | 60+6x=70+4x | | a+(a+15)=265 | | 3e^2+5e= | | 14(v+4)-2v=4(3v+2)-16 | | 8x-7=19+15+7 | | 9t-54=126 | | 4(x+3)-3=13 | | -3x-(x-6)=-6-4(5-x) | | (8-w)(3w+1)=0 | | -6(4x-5)=3(4x-4)+78 | | x+3=2xlog*6 | | m^2-1+2m=0 | | 3(x+2)(x+3)=0 | | 4x^2-3x=24-(3x-1) | | 5/14/5/6= | | 0.25(x+30)-0.03(x-20)=5.9 | | 4-4[4-(6y-2)]= | | 1/3x-2=-12 | | -10(x+7)+529=15+24 | | 6(2x-3)+9x= | | 2y+x=153 | | (2a+b)(5a-3)= | | 139+x+14=180 | | 3x-3x-2=-2 | | 5M-3(2M+7)=3M+12-5M | | 58+6x+2=180 | | H=-16t+52t+7 | | 110+3x+16=180 | | -m/5=5/2 | | 85+6x+5=180 | | X^2+x+3=90 |

Equations solver categories